Prime Ministers in Europe - Müller-Rommel, Ferdinand. author. aut Link
XX, 231 p. 32 illus.
Keywords: Even though the question of ‘who governs’ has been at the centre of political science research for a long time, a systematic comparative analysis of the profiles of prime ministers in Europe was missing. This data rich volume allows to put prime ministerial figures into perspective. Scholars will welcome the inspiring arguments on the careers of top executives. -Patrick Dumont – Professor of Political Science, Australian National University, Canberra. This is a formidable contribution to the study of prime ministers. Building on a unique database, this book shows that the nature of prime ministerial leadership has been drifting towards a more assertive role of chief executives vis-à-vis their own parties. It shows that the control of political parties over the process of government has been declining while political leaders have gained political weight. -Thomas Poguntke – Professor of Comparative Politics, Heinrich Heine University of Düsseldorf, Germany This book presents the first comparative analysis of European prime ministerial careers. It is the result of an ambitious data collection effort and presents significant cross-temporal and cross-national changes in the experience that prime ministers bring to the highest office. The book will, without doubt, become a key reference work for the study of executive careers. -Petra Schleiter – Professor of Comparative Politics, University of Oxford, UK This book examines the changes in the career experiences and profiles of 350 European prime ministers in 26 European democracies from 1945 to 2020. It builds on a theoretical framework, which claims that the decline of party government along with the increase of populism, technocracy, and the presidentialization of politics have influenced the careers of prime ministers over the past 70 years. The findings show that prime ministers’ career experiences became less political and more technical. Moreover, their career profiles shifted from a traditional type of ‘party-agent’ to a new type of ‘party-principal’. These changes affected the recruitment of executive elites and their political representation in European democracies, albeit with different intensity and speed. Ferdinand Müller-Rommel - Professor (Emeritus) of Comparative Politics at Leuphana University Lüneburg, Germany. Michelangelo Vercesi - Lecturer in Comparative Politics at Leuphana University Lüneburg, Germany. Jan Berz - Assistant Professor of Political Science at Trinity College Dublin, Ireland.